2005
DOI: 10.1200/jco.2005.03.111
|View full text |Cite|
|
Sign up to set email alerts
|

Invasive Lobular Carcinoma Classic Type: Response to Primary Chemotherapy and Survival Outcomes

Abstract: ILC is characterized by lower rates of pathologic response to PC but better long-term outcomes compared to IDC. pCR might not be a prognostic indicator for this group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

31
225
5
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 362 publications
(268 citation statements)
references
References 32 publications
31
225
5
7
Order By: Relevance
“…Contrary to other authors, we observed better DDFS and OS for ILC compared to non-ILC [10]. Only pCR patients with ILC had a significantly worse distant disease free survival compared with non-ILC, which might be biased by heterogeneity of baseline factors.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Contrary to other authors, we observed better DDFS and OS for ILC compared to non-ILC [10]. Only pCR patients with ILC had a significantly worse distant disease free survival compared with non-ILC, which might be biased by heterogeneity of baseline factors.…”
Section: Discussioncontrasting
confidence: 99%
“…Using data from 1,051 patients with ILC in this pooled analysis, it was shown that this cohort had a significantly lower pCR rate compared with non-ILC patients. However, biologically aggressive ILCs (HR-and G3) especially in younger patients achieved a pCR rate comparable to nonILCs [8,10,19,20]. Patients with lobular carcinomas were significantly more likely to receive a mastectomy even if a pCR was obtained after neoadjuvant chemotherapy [21][22][23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently shown that the response to primary chemotherapy is lower in terms of pCR in ILC compared with IDC, with a greater need for mastectomy for the former [21,22]. Conversely, the outcome of ILC appeared to be more favorable than for IDC [20].…”
Section: Discussionmentioning
confidence: 99%
“…ILBCs are mostly oestrogen receptor (ER)-positive and adjuvant endocrine therapy represents the treatment of choice [12]. Several studies have demonstrated the chemoresistance of ILBCs towards conventional anti-cancer agents [12][13][14], perhaps related to the slow proliferation of ILBC cells [13].…”
Section: Introductionmentioning
confidence: 99%